2015
DOI: 10.18805/ijar.5929
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different initial weights on fattening performance, slaughter and carcass characteristics of Holstein Friesian and Brown Swiss young bulls

Abstract: A total of 27 young bulls [13 Brown Swiss (BS) and 14 Holstein Friesian (HF)] were fed to investigate the effects of initial fattening weights [light weight group (LG= 176.0± 3.5 kg) and heavy weight group (HG= 213.8±3.7 kg)] on the performance, slaughter and carcass traits. With increasing initial fattening weight, final weight (P the initial fattening weights in favour of bulls in HG. Average SEUROP conformation score of HG carcasses was one class better than that of LG carcasses. It was concluded that young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…Accordingly, it can be seen that there is not much difference between the two studies for Charolais, while there is a quite difference for Galloway. Also, as Diler et al (2016) reported, although the general expectation is that the carcass weight will increase as the slaughter age increases, the opposite situation was observed when the study conducted by Filipcik et al (2015) study was compared with our study. In this case, it should be mentioned that the effect of the feeding regimen applied is that there are studies reporting that carcass weight is higher in intensive fattening systems compared to extensive or semiintensive fattening systems (Sari et al, 2015;Onk et al, 2017).…”
Section: Resultscontrasting
confidence: 79%
“…Accordingly, it can be seen that there is not much difference between the two studies for Charolais, while there is a quite difference for Galloway. Also, as Diler et al (2016) reported, although the general expectation is that the carcass weight will increase as the slaughter age increases, the opposite situation was observed when the study conducted by Filipcik et al (2015) study was compared with our study. In this case, it should be mentioned that the effect of the feeding regimen applied is that there are studies reporting that carcass weight is higher in intensive fattening systems compared to extensive or semiintensive fattening systems (Sari et al, 2015;Onk et al, 2017).…”
Section: Resultscontrasting
confidence: 79%
“…Meat colour parameters of beef are affected by a number of factors involving pre-and post-slaughter determinants and genotypic structure (Mancini and Hunt, 2005). Effects of breed, sex, nutrition, season, and preslaughter stress on meat yield and quality have been commonly studied (Aydin et al, 2013;Chambaz et al, 2003;Diler et al, 2016;Kadim et al, 2004;Wêglarz, 2010;. To the best of our knowledge, there is a limited information about the association between age at slaughter and colour coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…In the farms of our country, among the dairy breeds of cattle, the Ukrainian black and spotted dairy breed is the most concentrated. 1 . The fattening young have good meat indicators and at the age of 12 months reach a live weight of 380-400 kg, at the age of 18 months -500-520 kg.…”
Section: Introductionmentioning
confidence: 99%